Prospective Study on the Efficacy of Tamulosin in Medical Management of Distal Ureteric Stones - Basnet, S; Shrestha, PM; Shakya, Rajani (Journal of Chitwan Medical College, 2013)
A non-interventional prospective study was done in patients having single distal ureteral stone less than 10 mm to find the effectiveness of two weeks course of Tamsulosin 0.4 mg in the stone expulsion; the reduction of occurrence of ureteral, reduction in rate of use of analgesic agents and the side effects of the drug. Thirty patients, having stone size ≤ 10.0 mm were revealed initially by patient’s symptoms and then confirmed by ultrasonography (USG) followed by Intravenous Urography (IVU) radiographic images. The expulsion rate of distal ureteral stones having size ≤ 10.0 mm was found to be 76.66 % (27 out of 30), with only 26.66 % of analgesic consumption, with decrease in colic episodes by 36.66 % and lesser evidence of side effects. The expulsion rate for stone size less than 7.0 mm is 36.72 % with mean of expulsion days as 5.90±1.92. The expulsion rate for stone size more than 7.0 mm is 63.33 % with mean of expulsion days as 9.33±27. The correlation between the size and expulsion days is statistically significant with p-value of 0.00057 (p = 0.01). The observed side effects were orthostatic hypotension (26.7 %), headache (13.3 %), dizziness (6.7 %), sore throat (6.7 %) followed by fatigue (3.3 %), abnormal ejaculation (3.3 %) and no any side effect was observed in 56.7 % patients. Considering the economic value and its effectiveness, the MET using Tamsulosin 0.4 mg can be the possible intervention for the medical treatment of distal ureteral stones having less than 10 mm stone size. Journal of Chitwan Medical College 2013; 3(1): 56-61 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8468